Strategi pemberdayaan anak melalui komunitas literasi teras ngabaca di Kota Cirebon - Elly Malihah; Salsabila Firdaus; Pandu Hyangsewu (Departemen Pendidikan Sosiologi FISHIPOL UNY, 2024)
This study was motivated by the researcher’s interest in the Teras Ngabaca community’s concern for the education of children in the Kalijaga neighborhood. The Teras Ngabaca community’s concern for education stems from the observation that many children are not yet proficient readers. Thus, Teras Ngabaca serves as a facilitator for the community, helping to improve their quality of life by providing a space for non-formal education. This study aims to identify how the Teras Ngabaca community works to improve children’s literacy and empower the community in Kalijaga Village, Cirebon City. The research method used in this study is qualitative, employing a case study approach. Data collection techniques included observation, interviews, documentation, and a literature review. The results show that the Teras Ngabaca community’s strategy for improving children’s literacy begins with an introduction to the alphabet, followed by the “Buku Bacalah” series (volumes 1–3), and then proceeds to storybooks or folktales. Teras Ngabaca also employs a one-on-one teaching strategy.